(untitled) (Italian Journal of Public Health, 2008)
Objectives: The main objective of this study was to explore potential health-promoting work factors and their specific associations with self-rated general and mental health, life satisfaction, and low levels of musculoskeletal pain among women and men employed in the public sector. Methods: A questionnaire based survey was conducted among 2523 public employees (87% women) in 124 work places. The workplaces were distributed between five occupational sectors: the provincial hospital, schools, home care services, domestic/catering, and administrative services. The response rate was 92%. Analyses of variance were used to compare the mean scores of the groups. Spearman’s rank correlation test was used to assess the associations between the work factors and the health measures. Results: Many of the potential health promoting work factors were associated with the measures of self-rated health. However the correlations differed according to both gender and occupational sector. The main differences between the sectors were the characteristics of decision latitude-influence and learning- development with the best conditions in the administrative services and schools, and the worst in home care services. Men rated higher in decision latitude-influence than women and had significantly better “opportunities to learn new and to develop in the profession”. Having enough time to complete the work tasks had the highest overall correlation with good health. In addition good relations with and support of supervisors were crucial for well-being among the employees. Conclusions: The results highlight the importance of high levels of decision latitude-influence, learning- development, and a fair and impartial attitude among supervisors for the promotion of good health in public work places.